How to know when little kidneys are in trouble: a review of current tools for diagnosing AKI in neonates - Evans, Rebecca E.; Peterson, Jennifer; Kim, Jon Jin; Mahaveer, Ajit (Frontiers in Pediatrics, 2023)
Due to a plethora of risk factors, including prematurity, neonates are at risk for acute kidney injury (AKI) and, once established, AKI is associated with poor outcomes. The most widely used AKI biomarker is creatinine, despite research demonstrating creatinine to be a suboptimal tool for diagnosing neonatal AKI. This article uses an amalgamated case study to illustrate the inadequacies of creatinine for detection of preterm AKI and to present a range of novel AKI biomarkers relevant to the neonatal population. Clinical evaluation of novel AKI biomarkers is needed to improve precision and rapidity of AKI management in neonates.